Consequences of fetomaternal haemorrhage after intrauterine transfusion. Issue 6660 (26th November 1988) - Nicolini, U.; Kochenour, N. K.; Greco, P.; Letsky, E. A.; Johnson, R. D.; Contreras, M.; Rodeck, C. H.
Abstract : Fetomaternal haemorrhage was studied after 68 consecutive fetal intravascular transfusions performed in 20 patients with Rh isoimmunisation. alpha Fetoprotein concentration was assayed in maternal blood taken before, and immediately after each transfusion and three and 24 hours later. An increase of 50% or more in the concentration in any of the samples after transfusion was considered to indicate fetomaternal haemorrhage. Fetal alpha fetoprotein concentration in blood sampled before transfusion was also assayed and the amount of fetomaternal haemorrhage calculated. Fetomaternal haemorrhage occurred in 21 of 32 patients with an anterior placenta and in six of 36 with a posterior or fundal placenta. The mean estimated volume of haemorrhage was 2.4 ml, which was on average equal to 3.1% of the total fetoplacental blood volume. When the volume of fetomaternal haemorrhage at the first transfusion was greater than 1 ml there was a greater increase in maternal Rh (D) antibody titres and a greater fall in fetal packed cell volume. Sampling of fetal blood should not be routinely done early in patients with Rh isoimmunisation, and intrauterine transfusion should be delayed as long as possible. Sampling sites other than the placental cord insertion reduces the risk of fetomaternal haemorrhage.